2011
DOI: 10.1007/s10096-011-1406-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of three human adenovirus species in adults with acute respiratory infection in China

Abstract: Human adenoviruses (HAdVs) are recognized as causal agents in a wide range of human diseases. However, researchers lack sufficient data on the exact HAdV species and serotypes associated with adult acute respiratory tract infections (ARTIs). To detect and characterize HAdV infections in adults in China, clinical specimens were collected from 10,310 adults with ARTIs from May 2005 to July 2010. The partial HAdV hexon gene was amplified by polymerase chain reaction (PCR), sequenced, and phylogenetically analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…These findings are consistent with other studies that have also shown that pediatric populations with acute respiratory diseases are commonly infected with HAdV-1, HAdV-2, or HAdV-3 [10]. Furthermore, the literature also demonstrates that most adult populations with HAdV infections are predominantly infected with HAdV-3, HAdV-4, HAdV-7 and HAdV-11, with a few HAdV-1, HAdV-2, HAdV-6 and HAdV-14 cases [11]. Of note in this study, HAdV-11, HAdV-17 and HAdV-21 were only found among the adult population (age ≥ 18 years).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with other studies that have also shown that pediatric populations with acute respiratory diseases are commonly infected with HAdV-1, HAdV-2, or HAdV-3 [10]. Furthermore, the literature also demonstrates that most adult populations with HAdV infections are predominantly infected with HAdV-3, HAdV-4, HAdV-7 and HAdV-11, with a few HAdV-1, HAdV-2, HAdV-6 and HAdV-14 cases [11]. Of note in this study, HAdV-11, HAdV-17 and HAdV-21 were only found among the adult population (age ≥ 18 years).…”
Section: Discussionsupporting
confidence: 89%
“…Among them, species B (HAdV-3, -7, -11, and -14) were most common (77.9%), 24 which were similar to our adenovirous type detected in pneumonia. However, HAdV-11 was the most common in our study, especially in patients with ARDS.…”
Section: Discussionsupporting
confidence: 70%
“…The subspecies B1 adenoviruses HAdV-3 and HAdV-7 have occurred epidemically and contribute greatly to pediatric acute respiratory diseases (9,11,14,26). Identification of the NAb epitopes of HAdV-3 and HAdV-7 will be beneficial for developing recombinant bivalent HAdV-3/HAdV-7 vaccines and preventing outbreak of HAdV-3 and HAdV-7 infection.…”
Section: Discussionmentioning
confidence: 99%